Processos de aquisição da memória: a gênese do lugar: uma análise fenomenológica das relações de pertencimento do ser humano com o espaço - Martins, Giovanna Silveira Sartório (Universidade Federal de São Carlos, 2021)
The present work intended to gather information about how subjectivity and the sense of belonging structures itself on individuals towards space, giving it the attribute of place. In order to do so, a bibliographical survey and systematization of the methodological assumptions regarding perception phenomenology were made, based on the theoretical work of Merleau-Ponty, as well as the gathering of information about the topic in the field of geography, based specially on the works of Yi Fu Tuan and Milton Santos, regarding the perspective of the experience and the nature of space, respectively. The information was structured with the intent of staggering the concepts, in order to build layers of comprehension of the final proposal, starting from the theoretical assumptions about perception, the field of phenomena and limitations of the body as an object-subject, finally connecting to the concepts of geographic space and place, from the perspective of experience. From that, an integration of both concepts was made, proposing an interpretation of how subjectivity is structured on a subject similar to the concept of geographic space proposed by Milton Santos, and analysing the category ‘place’ based on this proposal of interpretation.
Memory acquiring processes: the genesis of place: an analysis of the belonging relations between human and space
Keywords: Espaço; Lugar; Percepção; Perception; Place; Space; CIENCIAS HUMANAS::GEOGRAFIA